Illusory Facets of Sport: The Case of the Duke University Basketball Team - Muniowski Łukasz; Jacheć Tomasz (Sciendo, 2017)
In the society of the spectacle, illusion is an omnipresent phenomenon. It is used to distract the masses from issues crucial to their existence and to support a system of oppression. However, there is also a "lighter" side of illusion: it creates celebrities and helps sell products (films, music albums, sneakers, etc.). While the connotation is that spectacle uses illusion in order to present the ordinary or negative as extraordinary and positive (e.g., promiscuous athletes talking about family values), it is also possible for a reverse illusory process to take place, resulting in the regular being presented as irregular (e.g., a physical player presented as "aggressive", such as Kermit Washington). Unlike the deliberate use of illusion by the architects of the spectacle, this reverse process happens spontaneously.